Predictive Factors for Catecholamine-Induced Cardiomyopathy in Patients with Pheochromocytoma and Paraganglioma - Wang, Yi; Yu, Xuerong; Huang, Yuguang (Frontiers in Endocrinology, 2022)
Objective: To investigate possible predictive factors of catecholamine-induced cardiomyopathy in pheochromocytoma and paraganglioma (CICMPP) patients. Methods: In all, 50 CICMPP patients and 152 pheochromocytoma and paraganglioma (PPGL) patients without CICMPP who were treated in our institution between August 2012 and April 2018 were included in this retrospective study to assess predictors of CICMPP. Results: Patients with CICMPP reported younger onset age, more clinical symptoms and signs, more family history of hypertension and higher maximum systolic, diastolic, and mean BP and maximum HR. Medical evaluation also showed higher level of blood hematocrit, blood glucose, 24h urine catecholamines, larger diameter of the tumor and more comorbidities, von Hippel-Lindau syndromes, and metastatic tumors in these patients. Multivariable analysis identified maximum resting HR over 115 beats/min (OR 10.05, 95% CI 3.71-27.20), maximum resting systolic BP over 180 mmHg (OR 7.17, 95% CI 2.22-23.23), blood glucose over 8.0 mmol/l (OR 6.52, 95% CI 2.25-18.86), more than 3 symptoms and signs (OR 6.05, 95% CI 1.86-19.64), and onset age under 40 years (OR 3.74, 95% CI 1.37-10.20) as independent predictors of CICMPP. Female sex (OR 5.06, 95% CI 1.19-21.54), complaint of chest pain (OR 5.84, 95% CI 1.27-26.90) and extra-adrenal tumor (OR 8.64, 95% CI 1.82-40.94) were independent predictors of Takotsubo cardiomyopathy in CICMPP. Conclusion: Maximum resting HR ≥115 beats/min, maximum resting systolic BP ≥180 mmHg, blood glucose ≥8.0 mmol/l, number of symptoms and signs ≥3, and onset age ≤40 years were found to be predictive factors for CICMPP.